Freedom within the coordinates of Ukrainian ideas in the 19th–21st centuries - Ушкалов, Леонід Володимирович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The paper deals with the concept of FREEDOM in the Ukrainian literary, intellectual and political tradition of the 19th–21st centuries, and proves that the conception according to which the characteristic feature of the Ukrainians’ outlook and the way of life is striving for freedom appeared in the age of romanticism. Moreover, the vision of world history presented in the program document of the Brotherhood of Saints Cyril and Methodius The Books of Genesis of the Ukrainian People (1847) is an apocatastasis of freedom, i.e. a story of human being’s “breaking with” freedom and coming back to it. The greatest achievement of the Ukrainian philosophy of freedom in the age of positivism was Mykhailo Drahomanov’s anarchism. Following Proudhon, Drahomanov treated anarchy as self-government and considered the anarchy in politics as an equivalent to the theory of evolution in natural history and sociology. However, during the 20th–the early 21st centuries Ukrainian intellectuals approached freedom mainly in terms of existential philosophy. This is especially noticeable in the understanding of freedom typical of the activists representing the Artistic Ukrainian Movement (1945–1948) and of the “men and women of the sixties”.